2013
DOI: 10.1007/s11356-013-1771-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on ammonium assimilation in soybean roots

Abstract: Bisphenol A (BPA), which is ubiquitous in the environment, is an example of an endocrine-disrupting compound (EDC). Ammonium assimilation has an important function in plant growth and development. However, insufficient information on the potential effect of BPA on ammonium assimilation in plants is available. In this study, the effects of BPA on ammonium assimilation in roots of soybean seedlings were investigated. During the stress period, 1.5 mg L(-1) of BPA improved glutamine synthetase (GS)/glutamate synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Therefore, nitrate assimilation in the soybean seedling roots that were treated with low-concentration BPA was unchanged, whereas the single treatment with lowconcentration BPA promoted nitrate uptake (Figure 2A) [10]. In this treatment, the improvement in soybean seedling root growth might be a result of the enhanced ammonia assimilation [10,11].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, nitrate assimilation in the soybean seedling roots that were treated with low-concentration BPA was unchanged, whereas the single treatment with lowconcentration BPA promoted nitrate uptake (Figure 2A) [10]. In this treatment, the improvement in soybean seedling root growth might be a result of the enhanced ammonia assimilation [10,11].…”
Section: Discussionmentioning
confidence: 95%
“…3). In this combined treatment, because of the decrease in the GS/GOGAT cycle and the increase in protein hydrolysis [75,76], there was still excessive accumulation of ammonium ion in roots, which caused damage despite the consumption of some of the ammonium through the GDH pathway [75,76]. After 5 days of recovery, the ammonia assimilation in the roots recovered to a certain extent (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…4). The increase in the amino acid content might be related to the promotion of the GDH pathway (Table 1) and the hydrolysis of soluble proteins [75,76]. The additional amino acids might be used to alleviate the toxic effects induced by the excess accumulation of ammonium [47,83].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to study the effects of BPA on plant roots. We previously reported the effects of BPA on nitrogen metabolism in soybean seedling roots [17,18]. In addition to nitrogen, other mineral elements (P, K, Ca, Mg, Fe, Mn, Cu, Zn, and Mo) are also necessary for plant growth and development.…”
Section: Accepted Preprintmentioning
confidence: 99%
“…), durum wheat and lettuce (Lactuca sativa L.) seedlings, moreover, root symptoms, including browning and the formation of jelly-like films, were also observed [12]. Some studies have demonstrated that treatment with 1.5 mg L -1 BPA promotes nitrogen assimilation in soybean (Glycine max L.) seedling roots [17,18] and…”
Section: Introductionmentioning
confidence: 99%